2005
DOI: 10.1021/bi0503798
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Chemistry in the GFP Active Site Leads to Covalent Cross-Linking of a Modified Leucine Side Chain with a Histidine Imidazole:  Implications for the Mechanism of Chromophore Formation,

Abstract: The mechanism of chromophore biosynthesis in green fluorescent protein (GFP) is triggered by a spontaneous main chain cyclization reaction of residues 65-67. Here, we demonstrate that the initially colorless Y66L variant, designed to trap chromophore precursor states, is oxidatively modified to generate yellow chromophores that absorb at 412 and 374 nm. High- and low-pH crystal structures determined to 2.0 and 1.5 A resolution, respectively, are consistent with pi-orbital conjugation of a planar Leu66-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…GFP folds into an 11-stranded β-barrel with a single helical segment threaded through the center of the barrel, and capped by several loops at either end of the barrel. A sharp turn places strain on three residues within the barrel-encapsulated stretch, which consequently drives cyclization via a dehydration/oxidation mechanism that requires only molecular oxygen678. The cyclized chromophore remains covalently attached to the polypeptide chain, and therefore, every cell expressing the GFP gene acquires fluorescence.…”
mentioning
confidence: 99%
“…GFP folds into an 11-stranded β-barrel with a single helical segment threaded through the center of the barrel, and capped by several loops at either end of the barrel. A sharp turn places strain on three residues within the barrel-encapsulated stretch, which consequently drives cyclization via a dehydration/oxidation mechanism that requires only molecular oxygen678. The cyclized chromophore remains covalently attached to the polypeptide chain, and therefore, every cell expressing the GFP gene acquires fluorescence.…”
mentioning
confidence: 99%
“…These compounds were able to diffuse into the protein's interior and accept a proton under physiological conditions (16, 17). Redox chemistry did not play a role in re-hybridization from sp 3 to sp 2 , rendering a radical mechanism for C β 66 oxidation unlikely (14). Here, we present further evidence that the chemistry observed in Y66L is analogous to the normal maturation mechanism of intact GFPs.…”
mentioning
confidence: 99%
“…We also found that the yellow species is generated from an intermediate that absorbs at 338 nm, and that formation of the 338-nm species is independent of oxygen. The X-ray structure of yellow Y66L indicated nearly complete elimination of water from the heterocycle (21). The electron density of the leucine side chain appeared to be in a near-planar conformation, most consistent with π-orbital conjugation of the side chain atoms with the heterocycle.…”
Section: The Mechanism Of Gfp Chromophore Formation Is Mimicked In Y66lmentioning
confidence: 83%
“…Procedures were carried out as described in reference (21). Colorless Y66L was converted to a UV/Vis absorbing form with yellow appearance by incubation in the presence of 2.0 M sodium formate.…”
Section: Preparation Of Yellow Egfp-y66lmentioning
confidence: 99%
See 1 more Smart Citation